Solvability of a second-order multi-point boundary-value problems at resonance on a half-line with dim ker L=2 - Weihua Jiang; Bin Wang; Zhenji Wang (Electronic Journal of Differential Equations, 2011)
We show the existence of solutions for a second-order multi-point boundary-value problem at resonance on a half-line, where the dimension of the kernel of the differential operator is 2. Our main tools are the coincidence degree theory due to Mawhin, suitable operators, and algebraic methods. Our results are illustrated with an example.